2019
DOI: 10.3390/ijms20071719
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fatty Acid Profiles in a Group of Female Patients with Chronic Kidney Diseases (CKD) and Metabolic Syndrome (MetS)–Similar Trends of Changes, Different Pathophysiology

Abstract: Fatty acid (FA) profiles in the plasma of patients with metabolic syndrome and chronic kidney disease (CKD) seem to be identical despite their different etiology (dietary mistakes vs. cachexia). The aim of this study was to compare both profiles and to highlight the differences that could influence the improvement of the treatment of patients in both groups. The study involved 73 women, including 24 patients with chronic kidney disease treated with haemodialysis, 19 patients with metabolic syndrome (MetS), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…Moreover, in MetS, auxiliary metabolic pathways are activated for oleic acid and cause the simultaneous inhibition of EPA and DHA synthesis from ALA, whereas in the CKD group, we observe increased synthesis of EPA and DHA. The higher increase of nervonic acid (C24:1) in CKD suggests a higher degree of demyelination and loss of anons [11].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, in MetS, auxiliary metabolic pathways are activated for oleic acid and cause the simultaneous inhibition of EPA and DHA synthesis from ALA, whereas in the CKD group, we observe increased synthesis of EPA and DHA. The higher increase of nervonic acid (C24:1) in CKD suggests a higher degree of demyelination and loss of anons [11].…”
Section: Introductionmentioning
confidence: 96%
“…In contradiction to that, two cohort studies performed by Targher et al showed that renal disfunction was significantly more frequent in patients with NAFLD [9,10]. The authors of the study already compared the FA profile of CKD patients with the profile of patients with Metabolic Syndrome (MetS); it was observed that there had been an increase in the amounts of all FAs in plasma in the CKD group, especially in the case of palmitic acid (C16:0) and the derivatives of stearic acid (C18:0), higher than in the MetS patients; this may result from the decomposition of adipose tissue and the progressing devastation of the organism [11]. Furthermore, stearoyl-CoA desaturase (SCD) is a reticulum enzyme that catalyzes of monounsaturated fatty acids from saturated fatty acids [12].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently described changes focus on cholesterol and triacylglycerols. Many studies, including our previous research, have also shown abnormal serum fatty acid (FA) profiles in patients with CKD [16][17][18]. Dyslipidemia observed in patients with CKD is one of the well-known risk factors of cardiovascular disease (CVD) or diabetes mellitus [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In an animal model stereological study, the authors revealed that 20% sesame oil might lead to renal deformities [43]. However, saturated FAts in animal oil caused insulin resistance which contributes to the development of CKD [44]. Interestingly, in our work, the moderate consumption of cooking oil (25-30 ml/d) had a positive effect on the CKD prevention regardless of the type of cooking oil.…”
Section: Discussionmentioning
confidence: 43%